Perspektif Variabilitas Pengauditan dan Employee Fraud Tendency pada Entitas Otomotif - Saifudin, Saifudin; Alinsari, Natasia (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2024)
The purpose of this study is to examine the effect of auditing variability proxied by fraud diamond, auditor experience and due professional care on employee fraud tendency in automotive entities. This research method uses quantitative methods, with primary data on internal auditors at PT Nusantara Sakti in West Java and Central Java. The results of this study indicate that fraud affects employee fraud tendency, while auditor experience and due professional care have no effect on employee fraud tendency.